Continuous Intention to Use E-wallet by Business Owners in the Context of the COVID-19 Pandemic - Eric S Parilla; Marc Edward Abadilla (Research Synergy Foundation, 2023)
This research paper aims to scan the relationship between perceived susceptibility, perceived severity, self-efficacy, perceived ease of use, perceived usefulness, adoption to satisfaction, and attitude towards the continuous use of e-wallets during the COVID-19 pandemic. The researchers opted to conduct a study on this because of the proliferation of the use of digital wallets in the Philippines, such as Maya, Gcash, and others. There are about 2,644 distributed questionnaires. The study included partial least squares structural equation modelling (PLS-SEM) and a questionnaire tailored to business owners' understanding and attitudes towards using e-wallets. The investigation revealed that perceived susceptibility, perceived ease of use, and perceived usefulness are related to satisfaction with using e-wallets. Moreover, satisfaction with using e-wallets is related to the attitude towards e-wallets. In addition, attitudes towards e-wallets impact business owners' continuous use of e-wallets in the Philippines. This means that because of the pandemic, business owners have a positive attitude toward the continuous use of e-wallets. The study recommends policymakers to continue monitoring e-wallet providers since it is a new scheme of payments.